2010
DOI: 10.1007/978-3-642-14162-1_27
|View full text |Cite
|
Sign up to set email alerts
|

On p-Optimal Proof Systems and Logics for PTIME

Abstract: Abstract. We prove that TAUT has a p-optimal proof system if and only if a logic related to least fixed-point logic captures polynomial time on all finite structures. Furthermore, we show that TAUT has no effectively p-optimal proof system if NTIME(h O(1) ) ⊆ DTIME(h O(log h) ) for every time constructible and increasing function h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In [4] we have shown that the logic LFP inv is a P-bounded logic for P if and only if LIST(P, TAUT, P). Here, among others, we show the L-analogue and the NL-analogue of this result.…”
Section: Listings and Logicsmentioning
confidence: 98%
See 2 more Smart Citations
“…In [4] we have shown that the logic LFP inv is a P-bounded logic for P if and only if LIST(P, TAUT, P). Here, among others, we show the L-analogue and the NL-analogue of this result.…”
Section: Listings and Logicsmentioning
confidence: 98%
“…Recently [4] we have shown for C = P that such a listing exists if there is a listing of the P-subsets of the set TAUT of propositional tautologies; more explicitly, a listing of the subsets in P of TAUT by means of polynomial time Turing machines deciding them. Even more, it is shown in [4] that the following two statements are equivalent:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show for arbitrary Q that the existence of hard sets for all algorithms is equivalent to the existence of an effective enumeration of all polynomial time decidable subsets of Q, a property which has turned out to be useful in various contexts (cf. [12,2,3]). We analyze what Messner's result means for proof systems.…”
Section: Introductionmentioning
confidence: 99%
“…In [3] we showed that TAUT has a p-optimal proof system if and only if a certain logic L ≤ is a P-bounded logic for P (=PTIME). The equivalence in the first line of Theorem 2 is the nondeterministic version of this result; in fact, an immediate consequence of it states that TAUT has an optimal proof system if and only if L ≤ is an NP-bounded logic for P (a concept that we will introduce in Section 6).…”
Section: P-gödelmentioning
confidence: 99%